1971
DOI: 10.1039/j39710000434
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic rearrangements. Part V. Transformations of 3,5-diacetyl-4-chloromethyl-1,4-dihydro-2,6-dimethylpyridine

Abstract: The title compound (Ia) undergoes the expected ring expansion to 3.6-diacetyl-4.5-dihydro-2.7-dimethyl-I Hazepine-4-carbonitrile (11) when treated with cyanide ion. When treated with water, (Ia) gives 3,5-diacetyl-4-(2-acetyl-3-oxobutyl)-1,4-dihydro-2,6-dimethylpyridine ( I I I a ) and a rearrangement product, 4-acetyl-2-(1 -acetyl-2-oxopropyl)-2,3-dihydro-5-methylfuran (V). Pyrolysis of the dihydrofuran (V) yields 3,6-bis-(1hydroxyethylidene)oct-4-ene-2,7-dione ( V I ) whereas hydrolysis gives the fulvene, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This reaction also occurred when the dihydropyridine 1 was treated with sodium cyanide in DMSO (20°C, 16 h) and resulted in the formation of the azepine 3 in nearly quantitative yield [23,24]. The azepines 11 [25], 12 [23], and 13 [26,27] were synthesized in a similar way, using the dihydropyridines 4-6, respectively, as substrates.…”
mentioning
confidence: 99%
“…This reaction also occurred when the dihydropyridine 1 was treated with sodium cyanide in DMSO (20°C, 16 h) and resulted in the formation of the azepine 3 in nearly quantitative yield [23,24]. The azepines 11 [25], 12 [23], and 13 [26,27] were synthesized in a similar way, using the dihydropyridines 4-6, respectively, as substrates.…”
mentioning
confidence: 99%
“…A reinvestigation of the action of cyanide ion on the diester l c revealed that ring expansion had taken place leading to a 4,5-dihydro-lH-azepine (4), and this was extended to the dicyano ( 5 ) and diacetyl compounds (6). Subsequent work has shown that the chloromethyl compounds may be used in the synthesis of azepines (7), pyrroles (4-7), fulvenes (8).…”
mentioning
confidence: 99%